Modified Small-Volume Jet Nebulizer Based on CFD Simulation and Its Clinical Outcomes in Small Asthmatic Children - Sermsri Santati; Jatuporn Thongsri; Parinya Sarntima (My University, 2019)
The small-volume jet nebulizer (SVJN) is an aerosol device used to treat respiratory illnesses. Major problems for aerosol treatment in small children include the penetration of particles to the lower lungs due to irregular and small volume of a child patient’s breath while the nebulizers used are the same models intended for adults. This adult SVJN produces a huge number of particles at a higher speed than small children can intake. To solve this problem, computational fluid dynamics (CFD) was used to redesign the device by adding 6-inch corrugated tube with 80 ml capacity (equal to one inhale capacity of a small child) into the traditional SVJN. Results revealed that the undulations of the corrugated tube were the important parts that change the direction of aerosol flow, slowing down the produced speed of aerosol up to 31.48% (mean speed = 0.37 m/s via modified SVJN vs 0.54 m/s via traditional which were close to measured results). The modified SVJN was tested for the effectiveness on how it could accommodate bronchodilator drug to the lower lungs by 3 clinical researches with 238 asthmatic children aged 1–5 years. The results revealed that the experimental group reported higher bronchodilatating effects: higher mean score of change in oxygen saturation and degree of wheezing and greater reduction in respiratory rate per minute than the control group with statistical difference (p<0.05). Meanwhile, heart rate and physical attributes (dead volume and duration of aerosol treatment) were indifferent. Moreover, small children showed more acceptance behavior towards this modified SVJN than the traditional one. Modified SVJN might be a good choice for aerosol treatment in small children because it slows down the speed of aerosol production, makes them well spread all over the reservoir, and is ready for small children to inhale for better clinical outcomes while physical attributes are the same.
Keywords: Nebulizer; Inhalation and Respiratory Drug Delivery